shRNA and siRNA Delivery to the Brain - Pardridge, William M. (2007)
The limiting factor in in vivo RNA interference (RNAi) is delivery. Drug delivery methods that are effective in cell culture may not be practical in vivo for intravenous RNAi applications. Nucleic acid drugs are highly charged and do not cross cell membranes by free diffusion. Therefore, the in vivo delivery of RNAi-therapeutics must using targeting technology that enables the RNAi therapeutic to traverse biological membrane barriers in vivo. For RNAi of the brain, the nucleic acid-based drug must first cross the brain capillary endothelial wall, which forms the blood-brain barrier (BBB) in vivo, and then traverse the brain cell plasma membrane. Similar to the delivery of non-viral gene therapies, plasmid DNA encoding for short hairpin RNA (shRNA) may be delivered to brain following intravenous administration with pegylated immunoliposomes (PILs). The plasmid DNA is encapsulated in a 100 nm liposome, which is pegylated, and conjugated with receptor specific targeting monoclonal antibodies (MAb). Weekly, intravenous RNAi with PILs enables a 90% knockdown of the human epidermal growth factor receptor, which results in a 90% increase in survival time in mice with intra-cranial brain cancer. Similar to the delivery of antisense agents, short interfering RNAi (siRNA) duplexes can be delivered with the combined use of targeting MAb’s and avidin-biotin technology. The siRNA is mono-biotinylated in parallel with the production of a conjugate of the targeting MAb and streptavidin. Intravenous RNAi requires the combined use of RNAi technology and a drug targeting technology that is effective in vivo.